Frequency of overweight and obesity in children and adolescents with autism and attention deficit/hyperactivity disorder - Kummer,Arthur (2016)
Abstract Objective: To assess the frequency of overweight and obesity in children and adolescents with autism spectrum disorder (ASD) and with attention deficit/hyperactivity disorder (ADHD) and their parents, in comparison with children and adolescents without developmental disorders. Methods: Anthropometric measures were obtained in 69 outpatients with ASD (8.4±4.2 years old), 23 with ADHD (8.5±2.4) and 19 controls without developmental disorders (8.6±2.9) between August and November 2014. Parents of patients with ASD and ADHD also had their anthropometric parameters taken. Overweight was defined as a percentile ≥85; obesity as a percentile ≥95; and underweight as a percentile ≤5. For adults, overweight was defined as a BMI between 25 and 30kg/m2 and obesity as a BMI higher than 30kg/m2. Results: Children and adolescents with ASD and ADHD had higher BMI percentile (p<0.01) and z-score (p<0.01) than controls, and increased frequency of overweight and obesity (p=0.04). Patients with ASD and ADHD did not differ between them in these variables, nor regarding abdominal circumference. Parents of children with ASD and ADHD did not differ between themselves. Conclusions: Children and adolescents with ASD and ADHD are at a higher risk of overweight and obesity than children without developmental problems in the community.